In‐phase antiguided bottom‐emitting vertical cavity laser arrays. Issue 14 (1st July 2013) - Johnson, M.T.; Siriani, D.F.; Leisher, P.O.; Choquette, K.D.
Abstract : In‐phase emission from a bottom‐emitting, coherently coupled, vertical cavity surface‐emitting laser array is demonstrated for the first time. Various array geometries are examined. An antiguided index profile is used to obtain the preferred on‐axis far‐field peak from a 2 × 1 array up to 0.9 mW, representing a critical step towards coherent, high‐brightness two‐dimensional laser arrays.